(untitled) (Jurnal Simki Economic, 2025)
This study aims to examine how accessibility, tourism experience, and tourist satisfaction influence the decision to revisit Gunung Rante Tourism, Banyuwangi. The increasing number of tourists visiting this destination shows the need to understand the factors that play a role in building visitor loyalty. This study uses a quantitative approach with a survey method on tourists who have visited Gunung Rante. Data were collected through questionnaires and analyzed using multiple linear regression to determine the effect of independent variables on the decision to revisit. The sampling technique used was purposive sampling. Based on the Lemeshow formula, the minimum number of samples needed in this study was 96 respondents. The results showed that accessibility plays a significant role in tourists’ decisions to return. Adequate infrastructure, such as good roads, easy transportation, and clear signs, contribute to travel comfort. Based on the test, accessibility (X₁) has a significant effect. Tourism experience (X₂) also has a significant effect. Tourist satisfaction (X₃) shows a positive impact. Thus, the better the accessibility, tourism experience, and satisfaction obtained, the higher the likelihood of tourists to revisit Gunung Rante.